Prevalence of Rhesus D negativity and barriers to immuno- prophylaxis among obstetric patients in Kitengela Sub- county Hospital: A cross-sectional study (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Rhesus (Rh) alloimmunization is a serious but preventable disease that develops in women who are Rh(D)-negative. This disease contributes significantly to perinatal morbidity and mortality. Prevalence data of Rh(D)-negative blood type among pregnant women in Kenya are scarce. This study aimed to determine the prevalence of Rh(D)-negative blood type, barriers to immunoprophylaxis, and ABO blood type patterns among the obstetric population in Kitengela Subcounty Hospital, Kajiado, Kenya.Methods: A cross-sectional study design was employed in which medical records of Rh-negative women as documented at the first antenatal visit were retrieved. Data were collected, extracted into a data collection tool, and analyzed using the Statistical Package for Social Scientists Software (SPSS version 23). Results: Of the 7141 women screened, 1.2 % (85) were Rh-negative. Among these, blood group O was the most common (48.2%), followed by blood groups B (24.7%), A (23.5%), and AB (3.5%). Most Rh-negative women (45.9%) were aged 15-23 years. Following delivery, only half of the women received anti-D immunoglobulin. Among those who did not receive anti-D postnatally, 80.8% lacked a documented reason, whereas 12.2% and 4.9% of the patients lacked access and did not know their Rh status, respectively. None of these patients had fetal blood grouping conducted before anti-D administration.Conclusion: Rh(D) negativity remains prevalent in the Kenyan population. However, access restrictions at both diagnostic and therapeutic levels remain. In addition, there is an overt hiatus in neonatal blood grouping.